Hazard assessment of insecticidal proteins representing different structural classes using an in vitro experimental platform of human intestinal epithelial monolayers - Cindi S. Zimmermann; Sujatha Rajeev Thundivalappil; Brittany Wilson-Mifsud; Sydney Boyle; Yiwei Wang; Ian Lamb; Matthew Merrell; Carey A. Mathesius; Melissa N. Fallers; JoAnna Bultman; Brenda L. Smith; Anne B. Carlson; et al. (Food and Chemical Toxicology, 2026)

Exploring policy coherence for land use transformations: The case of Scotland - Hebe Nicholson; Kirsty Blackstock; Jean Boucher; James Glendinning; Alexa Green; Alba Juarez-Bourke; Stan Martinat; Graciela Martínez Sánchez; Keith Matthews; Ian Merrell; Sam Poskitt; Steven Thomson (Journal of Environmental Management, 2025)

Earlier winter/spring runoff and snowmelt during warmer winters lead to lower summer chlorophyll‐ a in north temperate lakes - Allison R. Hrycik; Peter D. F. Isles; Rita Adrian; Matthew Albright; Linda C. Bacon; Stella A. Berger; Ruchi Bhattacharya; Hans‐Peter Grossart; Josef Hejzlar; Amy Lee Hetherington; Lesley B. Knoll; Alo Laas; et al. (Global Change Biology, 2021)
Winter conditions, such as ice cover and snow accumulation, are changing rapidly at northern latitudes and can have important implications for lake processes. For example, snowmelt in the watershed—a defining feature of lake hydrology because it delivers a large portion of annual nutrient inputs—is becoming earlier. Consequently, earlier and a shorter duration of snowmelt are expected to affect annual phytoplankton biomass. To test this hypothesis, we developed an index of runoff timing based on the date when 50% of cumulative runoff between January 1 and May 31 had occurred. The runoff index was computed using stream discharge for inflows, outflows, or for flows from nearby streams for 41 lakes in Europe and North America. The runoff index was then compared with summer chlorophyll‐ a (Chl‐ a ) concentration (a proxy for phytoplankton biomass) across 5–53 years for each lake. Earlier runoff generally corresponded to lower summer Chl‐ a . Furthermore, years with earlier runoff also had lower winter/spring runoff magnitude, more protracted runoff, and earlier ice‐out. We examined several lake characteristics that may regulate the strength of the relationship between runoff timing and summer Chl‐ a concentrations; however, our tested covariates had little effect on the relationship. Date of ice‐out was not clearly related to summer Chl‐ a concentrations. Our results indicate that ongoing changes in winter conditions may have important consequences for summer phytoplankton biomass and production.

Nano-Composite Foam Sensor System in Football Helmets - A. Jake Merrell; William F. Christensen; Matthew K. Seeley; Anton E. Bowden; David T. Fullwood (Annals of Biomedical Engineering, 2017)

Estimation of 3D Ground Reaction Force Using Nanocomposite Piezo-Responsive Foam Sensors During Walking - Parker G. Rosquist; Gavin Collins; A. Jake Merrell; Noelle J. Tuttle; James B. Tracy; Evan T. Bird; Matthew K. Seeley; David T. Fullwood; William F. Christensen; Anton E. Bowden (Annals of Biomedical Engineering, 2017)